Exploring the Influence of Financial Development, Institutional Quality and Trade Openness on Inclusive Growth in SAARC Countries - Asghar, Muhammad Muzammil; Safdar, Rabia; Zubair, Muhammad; Hanif, Muhammad (Pakistan Journal of Humanities and Social Sciences, 2024)
Better financial infrastructure, trade openness and quality of institutions are key to progress the economy. This paper investigates influence of financial development, institutional quality and trade openness on inclusive growth in SAARC countries during 1996 to 2020. The study applied different econometric techniques for data analysis such as panel unit root tests, Pedroni cointegration test, panel ARDL model and granger causality test. The results show that financial development, institutional quality and human capital are positively and significantly related to the inclusive growth while trade openness is negatively but insignificantly associated to the inclusive growth in SAARC countries. The causality analysis shows a unidirectional causality between EMP and IG, FD and inclusive growth, institutional quality and inclusive growth, human capital and inclusive growth while no causality is observed between TO and IG. Keeping in view the outcomes, it is suggested that financial development should be promoted, institutional quality should be improved and to curtail the negative impacts of trade on inclusive growth these countries should encourage the exports to improve their trade balance and inclusive growth.